FUNGSIONALISASI HUKUM PIDANA DALAM PELANGGARAN JADWAL KAMPANYE PEMILIHAN UMUM DEWAN PERWAKILAN RAKYAT DEWAN PERWAKILAN DAERAH dan DEWAN PERWAKILAN RAKYAT DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 2012 TENTANG PEMILIHAN UMUM DI KOTA PEKANBARU - Atika Pramuditha S; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Candidates for legislative elections is a form of political participation of the people in a democracy , the cleanliness , honesty and fairness of elections will reflect the quality of democracy in the country concerned . In order to protect the purity of legislative candidates were very important for democracy.Problems in this thesis is how the functionalization of criminal law in violation of the house of representatives election campaign schedule council and parliament by law number 8 of 2012 on the election of Pekanbaru ? Barriers to what is found in implementing the functionalization of criminal law in violation of the house of representatives election campaign schedule dpd and dprd based , law number 8 of 2012 concerning the elections in the city of Pekanbaru ? Any attempt to overcome the barriers to implementing the functioning of the criminal law in violation of the house of representatives election campaign schedule council and parliament by Law number 8 of 2012 on the elections in the city of Pekanbaru? whatever penelitihan goal is to know the functioning of the criminal law in violation of the house of representatives election campaign schedule council and parliament by law number 8 of 2012 on the elections in the city of Pekanbaru, to know the obstacles found in carrying out functionalization of criminal law in violation parliament election campaign schedule DPD and DPRD based , Law number 8 of 2012 concerning the elections in the city of Pekanbaru and to know what legal remedies if there are obstacles to overcome in implementing the criminal law against violations of the House of Representatives election campaign schedule Council and Parliament by Law number 8 of 2012 on the general election in the city of Pekanbaru.This type of research can be classified as socio-juridical, because in this penelitihan direct writing penelitihan held at the location or place under study in order to provide a complete and clear picture of the problems studied. Location research of Panwaslu, Bawaslu, KPU and Kepolisian the city of Pekanbaru. The data collection techniques with interviews and a literature.Based on the results of the study showed that in the implementation of the law enforcement criminal offense general election candidates in the implementation of the campaign schedule in Pekanbaru City 2014. not run in accordance with the applicable rules because there are obstacles in the implementation. The obstacle is : There are limitations to a very short time that is later than 7 days after the election violations and limitations of personnel and the ability to conduct the investigation in no way owned by members of the Election Supervisory Committee, does not have the authority to search and foreclose. Its made in overcoming obstacles are : Delivering quality elections , affirmation and synchronization between peruu existing regulations.Keywords: establishment - Criminal Act - General Elections